2001
DOI: 10.1520/jfs15014j
|View full text |Cite
|
Sign up to set email alerts
|

The Detection of Psilocin in Human Urine

Abstract: Pharmacokinetic studies of psilocybin in humans have shown the rapid dephosphorylation of psilocybin to psilocin with further conversion to 4-hydroxy-tryptophole (4HT) and 4-hydroxyindole-3-acetic acid (4HIAA) in plasma. Our study shows that psilocin also undergoes conjugation and can be found in the urine as the psilocin-glucuronide conjugate. Recoveries after enzymatic hydrolysis of the urine with β-glucuronidase (Helix Pomatia or E. Coli) when compared to non-hydrolyzed urine confirmed the presence of the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 5 publications
2
37
0
3
Order By: Relevance
“…In 1961 and 1962, psilocybin was reported to be rapidly dephosphorylated to form psilocin by phosphatase in human bodies [10,11]. Sticht and Käferstein [12] and Grieshaber et al [13] reported the analysis of psilocin in serum and urine specimens from magic mushroom abusers. Administration experiments also showed the conversion of psilocybin into psilocin in healthy volunteers [14][15][16].…”
Section: Metabolism In Humansmentioning
confidence: 99%
“…In 1961 and 1962, psilocybin was reported to be rapidly dephosphorylated to form psilocin by phosphatase in human bodies [10,11]. Sticht and Käferstein [12] and Grieshaber et al [13] reported the analysis of psilocin in serum and urine specimens from magic mushroom abusers. Administration experiments also showed the conversion of psilocybin into psilocin in healthy volunteers [14][15][16].…”
Section: Metabolism In Humansmentioning
confidence: 99%
“…Elle est ensuite transformée en 4-hydroxyindole-acétaldéhyde (4-HIA) puis en acide 4-hydroxyindole-3-acétique (4-HIAA) et en 4-hydroxytryptophol (28). Le dérivé glycuroconjugué de la psilocine prédomine dans l'urine mais n'est pas toujours mis en évidence (28,39,40). Ce métabolisme est représenté sur la Figure 2.…”
Section: Métabolisme De La Psilocybine Chez L'hommeunclassified
“…Les méthodes utilisées sont la CLHP avec un détecteur électrochimique, sur une colonne Spherisorb RP-8 par exemple (29,41,54), mais un système REMEDi HS a déjà été utilisé avec succès pour doser la psilocine dans l'urine (39). La CG-SM après dériva-tion est très performante, avec le proadifen ou la morphine deutérée comme étalon interne (39,40,49,50 Enfin, après leur création par un descripteur initial, certaines espèces ne sont pas retrouvées avant de nombreuses années. Entre temps, elles peuvent sembler être des espèces fantômes ou les contours de leur définition peuvent devenir assez flous.…”
Section: Dosages De La Psilocine Dans Les Milieux Biologiquesunclassified
“…Therefore, it is necessary to analyse body fluids from suspected drivers to prove an abuse of drugs like psilocin. Different chromatographic methods have been described for the detection of psilocin in body fluids: REMEDi HS as a drug screening method based on HPLC [6], HPLC with electrochemical detection [5,7,8], GC-MS [6,9], liquid chromatography with APCI-MS [10] and LC-MS-MS [11]. While the determination of psilocin in urine can be performed without sample clean-up, the analysis in plasma or serum requires an extraction procedure, followed by derivatisation of the extracts in the case of GC-MS.…”
Section: Introductionmentioning
confidence: 99%